Field Accumulation in Selected Heavy Metal Ions and Associated Health Risks in Irrigation Water, Soil and Tomatoes Collected from Homa Hills, Homabay County, Kenya - Akenga, T.; Ayabei, K.; Kerich, E.; Kandie, P.; Sudoi, V. (Africa Environmental Review Journal, 2022)
Accumulation of metal ions in irrigation water and soils can lead to uptake by food crops. The accumulated heavy metals when ingested pose a threat to human health. The current study intends to assess potential health risk of heavy metal contaminations in irrigation water, soil and tomatoes collected from Homa Hills, Rachuonyo North Sub- County, Homabay County, Kenya. Purposive sampling method was used to collect 10 tomato samples, 10 soil samples and 8 irrigation water samples. The following metal ions were investigated in the tomato, soil and irrigation water samples Chromium (Cr), Zinc (Zn), Cadmium (Cd), Manganese (Mn), Lead (Pb), Copper (Cu), Cobalt (Co) and Iron (Fe). The levels of the metal ions present in the samples collected were determined and quantified using Inductive Couple Plasma-Optical Emission Spectroscopy (ICP-OES) Perkin Elmer model 8000 DV. The results revealed that all the metal ions concentrations in tomatoes were beyond WHO recommended values except Co. The concentrations of all the metals in the soil were within the recommended levels in agricultural soil. In the irrigation water samples, the concentration of the metal ions was within the recommended values in irrigation water except Fe and Co. t-statistic revealed that the concentration of the metal ion in the tomatoes collected from the two locations (Kanam B and Kokoth Kata) of Rachuonyo North Sub-County did not vary significantly. The concentration of Zn, Cd, Co, Pb, Fe and Cu in tomatoes and irrigation water were significantly different except for Mn (p=0.06). The average concentration of metals in soil and water were significantly different. The calculated translocation factor (TF) for Fe, Cd, Cu and Zn was greater than 1 whereas Co, Pb and Mn TF<1. The concentration of Pb, Mn and Cu in soil and tomatoes showed weak positive correlation whereas all the other had negative correlation. The concentration of all the metals in water and tomatoes showed negative correlation except Co that showed weak positive correlation. The health risk index (HRI) for all the studied metals were less than 1 except for Cd, however, on computation of total target hazard quotient (THQ) the values for all the metals were less than 1. The study reveals that the presence of these metals did not pose any health risk. Since Cd had high values of both HRI and THQ relative to other metals further monitoring to establish its’ source is recommended.